1992
DOI: 10.1067/mva.1992.38645
|View full text |Cite
|
Sign up to set email alerts
|

Is anticoagulation indicated for asymptomatic postoperative calf vein thrombosis?

Abstract: The purpose of this study was to determine the effect of anticoagulation on the incidence of thrombotic propagation and pulmonary embolism in patients with calf vein thrombosis after total hip or total knee arthroplasty. Patients undergoing arthroplasties had prospective surveillance for postoperative deep vein thrombosis by both bilateral contrast venography and venous duplex scanning. Calf vein thrombosis was documented by venography in 42 patients (50 limbs), including 29 of 253 patients undergoing total hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Older studies of inpatients, outpatients and postoperative patients found variable proximal extension rates between 0% and 29% without treatment. This wide range is likely to be the consequence of study design (small, retrospective studies), population characteristics (patients with or without concomitant PE, variable rates of malignancy, variable rates of prior VTE), diagnostic tests used (venography vs. impedance plethysmography testing vs CUS) and follow-up duration [15][16][17][18][19][20][21][22].…”
Section: Proximal Extensionmentioning
confidence: 99%
“…Older studies of inpatients, outpatients and postoperative patients found variable proximal extension rates between 0% and 29% without treatment. This wide range is likely to be the consequence of study design (small, retrospective studies), population characteristics (patients with or without concomitant PE, variable rates of malignancy, variable rates of prior VTE), diagnostic tests used (venography vs. impedance plethysmography testing vs CUS) and follow-up duration [15][16][17][18][19][20][21][22].…”
Section: Proximal Extensionmentioning
confidence: 99%